Creating policies for results : (American Library Association, 2003)
Contain includes: create sound and legally defensible policies; customize policies appropriate to your library's specific mission, customers, and size using proven work forms; serve customers more effectively by updating, clarifying, and communicating new and revised policies; address needs of a changing customer base; create guidance and contingency plans for emergencies; add details and enforcement procedures for as many situations as possible.